Introduction to the special issue: Nonlinear effects and dynamics in close relationships. (October 2022) - Girme, Yuthika U; Overall, Nickola C; Simpson, Jeffry A
Relationship processes often involve fluctuating, variable, or tumultuous dynamics. Yet, close relationship models have traditionally focused on linear processes. The purpose of this Journal of Social and Personal Relationships special issue is to provide examples of how modeling nonlinear effects and dynamics can: (I) test nonlinear theoretical assumptions, (II) reconcile inconsistencies and reveal novel effects, (III) detect dynamic shifts in core relationship constructs, and (IV) capture temporal and spatial synchrony between partners within dyads. By showcasing a variety of nonlinear applications, we hope to encourage close relationship scholars to utilize similar nonlinear methods in order to advance relationship science by discovering common and important, but currently under-examined, relationship processes.